ORGINAL ARTICLEAutophagy – a basic mechanism and a potential role for neurodegeneration - Bursch, Wilfried; Ellinger, Adolf (Folia Neuropathologica, 2005)
Autophagy constitutes a fundamental survival strategy of cells; its disturbance contributes to the pathogenesis of cancer, liver and immune disease, pathogen infection, myopathies as well as neurodegenerative disorders such as Amyotrophic lateral sclerosis, Parkinson`s, Huntington`s and Alzheimer`s disease. The pathogenesis of neurodegenerative diseases also involves a gradual and progressive loss of neuronal cells. Cells may use different pathways for active self-destruction as reflected by different morphology: while in apoptosis (or “type I”) nuclear fragmentation associated with cytoplasmic condensation but preservation of organelles is predominant, autophagic degradation of the cytoplasmic structures preceding nuclear collapse is a characteristic of a second type of programmed cell death (PCD). Linking autophagy to programmed cell death initiated a controversial discussion on how a suggested role of autophagy in cell suicide might meet with its established survival function. To some extent, the diverse morphologies can be associated with distinct biochemical and molecular events [caspase-dependent and -independent death programs, DAP-kinase activity, Ras-expression, induction of autophagy genes, fate of cytoskeleton, among others]. However, there is a broad overlap between cell death pathways. Conceivably, diverse PCD programs emerged during evolution, the conservation of which allows eukaryotic cells a flexible response to physiological or pathological demands.